Public Health Outcomes through Medical Social Work: A Focus on Common Bacterial Infections - Izah, Sylvester Chibueze; Jacob Jack, Tarvie (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2024)
This study examines the vital role that medical social work plays in enhancing public health outcomes, with a focus on common bacterial illnesses. As the connection between infectious diseases and mental health is explored, the role of medical social workers in the psychosocial treatment of conditions such as TB, syphilis, Lyme disease, and streptococcal infections is emphasized. These bacterial infections are frequently associated with significant psychological suffering, including depression, anxiety, cognitive deterioration, and other mental diseases. This highlights the need for a comprehensive, all-encompassing treatment plan that considers patients’ physical and mental health requirements. Through interdisciplinary teamwork, medical social workers play a crucial role in improving access to resources, addressing social determinants of health, and supporting patients’ mental and physical well-being This approach fosters resilience in affected populations, improving long-term health outcomes. The paper also advocates for policy reforms incorporating medical social work into public health systems to effectively manage infectious diseases and their mental health impacts. How to cite this article: Jack T J, Izah S C. Public Health Outcomes through Medical Social Work: A Focus on Common Bacterial Infections. J Adv Res Psychol Psychother. 2024;7(1&2):6-20. DOI: https://doi.org/110.24321/25815822.202402